Sosialisasi Budidaya Buah Naga Untuk Daerah Pesisir di Desa Cintaratu, Parigi, Kabupaten Pangandaran - Sudarjat Sudarjat; Vijaya Isnaniawardhani; Muhamad Abdilah Hasan Qanit; Syariful Mubarok (Jurnal Pengabdian Pada Masyarakat, 2017)
SOCIALIZATION OF DRAGON FRUIT CULTURE FOR COASTAL REGION IN CINTARATU VILLAGE, PARIGI, DISTRICT OF PANGANDARAN. Dragon fruit is one type of potential fruits to be developed in the lowlands such as Pangandaran. Knowledge of dragon fruit cultivation in this area. An effort for the process of empowerment and community development for dragon fruit cultivation is with the socialization activities about the technology of dragon fruit cultivation. The purpose of this activity is to introduce dragon fruit plants to be cultivated in coastal areas of Pangandaran as one of the sources of food that rich with nutrition and support the improvement the nutrition of the community and allows to be an additional income for community. This activity was conducted in Cintaratu Village, Parigi, Pangandaran City by seminar and making the demonstration plot. The seminar was introduction of dragon fruit, explanation about the superiority and importance of dragon fruit as a source of nutrition, and also technology of dragon fruit cultivation in coastal area. In addition to making the demonstration plot (demplot) of dragon fruit on farmers' land. The results of this activities showed that there looks enthusiastic society to know more about what is the dragon fruit and how the dragon fruit culture techniques, so the dragon fruit in the area can develop. Keywords: Community, Cultivation, Dragon fruit, Pangandaran.